Pelatihan Pembuatan Lilin Aromaterapi untuk Meningkatkan Kreativitas dan Kemandirian Ekonomi Ibu-ibu PKK Desa Donohudan Kabupaten Boyolali - Ariyani Dwi Astuti; Vira Nur Lita; Chindy Martha Indhati; Sely Maisyah; Diva Maheswari; Annisa Indah Mutiasari (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this activity is to increase the creativity and economic independence of PKK mothers in Dusun II, Donohudan Village through aromatherapy candle making training. One of the problems faced is limited access to information, training, and entrepreneurial knowledge that limits the development of the economic potential of women in rural areas. The approach taken is through training that prioritizes direct practice, which includes the theory and method of making aromatherapy candles, with an emphasis on creativity and innovation. The results of this training show that all participants are actively involved and demonstrate the ability to understand and apply all steps in the candle making process, which produces varied and unique products. This training model can be recommended for women's empowerment in other locations and can be an example in the development of a creative economy based on local skills.